The Effectiveness of Whatsapp on Problem Posing Learning towards Students' Motivation and Cognitive Learning Outcome in Stoichiometry Topic - Safi’isrofiyah Safi’isrofiyah; Endang Budiasih; Surjani Wonorahardjo (Jurnal Pendidikan Sains, 2017)
Abstract: The objective of the study is to determine the differences in motivation and cognitive achievement between groups of students that learned with Problem Posing-WhatsApp model with group of students that learned with the Problem Posing only in Stoichiometry material. The research design used a quasi-experimental design without pre-test. Experiment class learned with Problem Posing by using WhatsApp learning model while the control class learned with Problem Posing learning model. Instruments measuring cognitive learning outcomes in the form of objective tests are 25 questions and motivation questionnaire with total 34 statements. The results showed that there are differences in motivation and cognitive achievement among students that learned with Problem Posing-WhatsApp learning model with group of students with Problem Posing model. Students that learned with Problem Posing by using WhatsApp learning model has an average of 79.67 and a motivation for cognitive achievement of 79.25, while the group of students that learned with Problem Posing learning model has an average of 73.89 and motivation for learning outcomes cognitive at 71.74.Key Words: problem posing learning model, WhatsApp, motivation, cognitive learning outcomes, stoichiometryAbstrak: Penelitian ini bertujuan mengetahui perbedaan motivasi dan hasil belajar kognitif antara kelompok siswa yang dibelajarkan model Problem Posing-WhatsApp dengan yang dibelajarkan model Problem Posing pada materi stoikiometri. Rancangan penelitian yang digunakan rancangan eksperimental semu tanpa pre tes. Instrumen pengukuran hasil belajar kognitif berupa tes objektif berjumlah 25 soal dan angket motivasi berjumlah 34 pernyataan. Hasil penelitian menunjukkan ada perbedaan  motivasi dan hasil belajar kognitif antara kedua kelas. Siswa yang dibelajarkan dengan model Problem Posing -WhatsApp memiliki rata-rata motivasi sebesar 79,67 dan hasil belajar kognitif sebesar 79,25, sedangkan kelompok siswa yang dibelajarkan dengan model Problem Posing memiliki rata-rata motivasi sebesar 73,89 dan hasil belajar kognitif sebesar 71,74. Kata kunci: model pembelajaran Problem Posing, WhatsApp, motivasi, hasil belajar kognitif, stoikiometri